2019
DOI: 10.1089/heq.2018.0089
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception and Cost-Effectiveness of a Patient Navigation Program to Improve Breast Cancer Screening for Hispanic Women

Abstract: Purpose: Hispanic women are less likely to be screened for breast cancer than non-Hispanic women, which contributes to the disproportionate prevalence of advanced-stage breast cancer in this population group. Patient navigation may be a promising approach to help women overcome the complexity of accessing multiple health care services related to breast cancer screening and treatment. The goal of this study is to assess patient perception and cost-effectiveness of a multilevel, community-based patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(87 citation statements)
references
References 26 publications
(28 reference statements)
1
81
0
Order By: Relevance
“…Additionally, early cervical cancer has no obvious symptoms, which therefore increases the difficulty of diagnosis [7]. In order to combat this disease, not only improved early diagnosis is requirement, novel and promising therapeutic targets are also urgly needed [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, early cervical cancer has no obvious symptoms, which therefore increases the difficulty of diagnosis [7]. In order to combat this disease, not only improved early diagnosis is requirement, novel and promising therapeutic targets are also urgly needed [8].…”
Section: Introductionmentioning
confidence: 99%
“…60,61 A cervical cancer screening patient navigation program tailored to vulnerable populations found navigation to be cost-effective compared to usual care. 62 A capitated payment lung cancer treatment patient navigation program for Medicare patients was cost-effective with an incremental cost-effectiveness ratio of $19,312 per quality-adjusted life year. 63 A patient navigation program at Henrico Doctors' Hospital found a navigation model assigning breast cancer patients to a navigator at time of suspicious finding through 12-months post diagnosis was effective in increasing revenue, standardizing care, and increasing patient retention throughout the care continuum.…”
Section: Discussion and Identifying Key Quality Metrics For Patient Nmentioning
confidence: 99%
“…37,38,39 Additionally, studies that have considered the specific cost effectiveness or cost savings associated with navigation services show positive trends. 40,41,42 Results from a cost-effectiveness (CE) analysis of the Chicago Cancer Navigation Project (CCNP), 43 a CE study of a navigation program to improve cervical cancer screening among Hispanic women in San Antonio, Texas, 44 and a CE analysis of a capitated navigation program for Medicare beneficiaries with lung cancer 45 all supported the cost effectiveness of navigation programs in breast, cervical, and lung cancer, respectively. Other health care cost analyses performed on government funded navigation programs such as the Center for Medicare & Medicaid Innovation (CMMI)-funded Health Care Innovation Awards (HCIA), 46 and the National Cancer Institute (NCI) Patient Navigation Research Program (PNRP) 47 have also shown promising trends in the impact of navigation services.…”
Section: The Case For Navigation: Impact Of Patient Navigators On Heamentioning
confidence: 99%